Effects of adopting IFRS 9 for the audit of financial instruments in non-financial companies - Silva, Shirley Franco da; Dantas, José Alves (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Objective: The aim of this study is to determine the effects of adopting IFRS 9 for the auditing of financial instruments in non-financial companies in Brazil. Methodology: The empirical tests were based on the data obtained from 338 non-financial companies listed in the B3 (Stock Exchange) in the period from 2014 to 2021, that appeared in the financial statements and auditing reports on the CVM website. The statistical tests were conducted in two stages: i) a descriptive analysis, through a comparison of the number of references to financial instruments, including the reasons for any alteration of opinion in the pre- and post- IFRS 9 periods; and ii) hypothesis testing of research by means of logistic regression estimates. Results: The results of the empirical tests revealed that the adoption of IFRS 9 is positively related to the references to financial instruments in the auditing reports, although they have not led to a rise in the number of altered opinions. Contributions made by the study: The empirical evidence arising from the literature on the auditing of financial instruments makes it possible to determine how the introduction of new accounting standards has affected the process of auditing and enabled the regulators and users of the information to understand the possible outcomes of regulations on the audit procedures for financial instruments. In addition, the findings made clear what factors determine how the adoption of IFRS 9 has affected the audit reports and the work they involve. They fill a gap in the literature with regard to the direct bearing IFRS 9 has on non-financial entities, given the fact that previous studies have concentrated on other aspects of the auditing of financial instruments and almost always been concerned with financial institutions.